CHILDREN'S FOLKLOR LITERATURE IN ELEMENTARY SCHOOL CHILDREN - Halimatussakdiah Halimatussakdiah (JGK (Jurnal Guru Kita), 2023)
Children's literature studies need to be developed in schools. This is reasonable because literature has an important role in building children's character. Literary literacy has the scope of empowering elementary school children to love literature, one of which is folklore. Folklore is a vehicle for achieving goals in understanding various aspects of life, acting as a step in preserving existing local culture. This is felt to be necessary at this time because many of the younger generation have forgotten the culture which is the heritage of their ancestors and the pride of their identity. Children prefer to watch television or play games on cell phones. Teachers' knowledge of literature is very low, literature is taught by unprofessional teachers, teachers do not understand how to teach literature well, teachers have not taught with appropriate strategies in literary literacy. Elementary school is the main means for developing literary literacy. Elementary school is an important means of balancing the development of character education while continuing to teach everything related to good values. One of the processes that includes learning is literary literacy. Teacher creativity in literary literacy learning needs to be increased because with creative literature teachers it is hoped that the literary learning that occurs will really be liked by children. Likewise, the local government's political attention must be to appreciate and accommodate literary literacy in schools, study groups, libraries and reading houses.